Population density of Beauveria bassiana in soil under the action of fungicides and native microbial populations (Acta Scientiarum. Agronomy, 2017)
This study investigated whether populations of naturally-occurring soil bacteria, fungi and actinomycetes influence the effect of fungicides on the survival and growth of Beauveria bassiana. The toxicity of methyl thiophanate, pyraclostrobin, mancozeb and copper oxychloride at the recommended doses was analyzed in culture medium and in soil inoculated with fungus at various time points after addition of fungicides. All fungicides completely inhibited the growth and sporulation of B. bassiana in the culture medium. The fungicides were less toxic in soil, emphasizing the action of the microbial populations, which interfered with the toxic effects of these products to the fungus. Actinomycetes had the greatest influence on the entomopathogen, inhibiting it or degrading the fungicides to contribute to the survival and growth of B. bassiana in soil. Native populations of fungi and bacteria had a smaller influence on the population density of B. bassiana and the action of fungicides towards entomopathogen. The toxic effect of the fungicides was greater when added to the soil one hour before or after inoculation than at 48h after inoculation.